Social Resilience in the Face of Climate Crisis: Comparative Insights from Kenya and Ethiopia - Kamau, David; Odhiambo, Emmanuel (Socio-political Communication and Policy Review, 2025)
This study explores the dynamics of social resilience to climate change through a comparative analysis of Kenya and Ethiopia—two East African nations facing increasing climate variability and environmental stress. Drawing on secondary data from academic literature, policy documents, and development reports, the research examines how national policies, community-based initiatives, and livelihood strategies contribute to resilience-building in diverse socio-political contexts. Kenya’s decentralized, participatory approach emphasizes local agency, traditional knowledge, and grassroots institutions, while Ethiopia’s state-led model integrates large-scale social protection and environmental restoration programs. The analysis reveals that both countries have made significant strides in enhancing resilience, yet face persistent challenges including funding gaps, implementation bottlenecks, and the under-recognition of non-economic losses such as cultural erosion and displacement. The study concludes that effective resilience strategies must be inclusive, context-sensitive, and adaptive, combining top-down coordination with bottom-up innovation. The findings offer valuable insights for policymakers, practitioners, and researchers seeking to strengthen social resilience in climate-vulnerable regions.